Determinants of Economic Dynamism among the 22 Municipalities in the Philippines - Capulong, Charlyn M.; Abing, Martha Joy J.; Teves, Maria Rizalia Y.; Babanto, Gerrich Aldin C. (Universitas Muhammadiyah Yogyakarta, 2024)
This study was conducted to identify the determinants of economic dynamism as proxy to investment climate of the 22 Municipalities in the Philippines. The variables namely infrastructure pillar, government efficiency pillar, and resiliency pillar from the Cities and Municipalities Competitiveness (CMCI) Survey are the independent variables considered in the study. Using panel regression in the analysis, the results show that economic dynamism is significantly driven by government efficiency and infrastructure pillars. Furthermore, the study revealed that economic dynamism scores of the Municipalities are increasing overtime as shown by the time effect component in the model. This suggests that the municipalities had improved their business climate over time, even during the pandemic. Based on the results, it is recommended that local government units (LGUs) focus on improving their performance under the indicators of government efficiency and infrastructure pillar to create a more business-friendly environment and attract more investors. Additionally, while the resiliency pillar did not show a statistically significant effect on economic dynamism, further review and enhancement of the indicators measuring resilience were suggested to better capture its impact.